2021
DOI: 10.1021/acsami.1c12243
|View full text |Cite
|
Sign up to set email alerts
|

A Naturally Derived Nanocomposite Film with Photodynamic Antibacterial Activity: New Prospect for Sustainable Food Packaging

Abstract: Food packaging with efficient antibacterial ability is highly desirable and challenging in facing the crisis of microbial contamination. However, most present packaging is based on metal-based antibacterial agents and requires a time-consuming antibacterial process. Here, the unique packaging (CC/BB films) featuring aggregation-induced emission behavior and photodynamic inactivation activity is prepared by dispersing self-assembled berberine–baicalin nanoparticles (BB NPs) into a mixed matrix of sodium carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…It also stands to reason that the CC/BB film’s low WVP and hydrophobicity are synergistic, thereby reinforcing one another. The compact framework of the CC film and CC/BB films could further contribute to their improved water vapour barrier performance [ 80 ].…”
Section: Factors Affecting Hydrophobicity Of Carrageenan Bionanocompo...mentioning
confidence: 99%
See 1 more Smart Citation
“…It also stands to reason that the CC/BB film’s low WVP and hydrophobicity are synergistic, thereby reinforcing one another. The compact framework of the CC film and CC/BB films could further contribute to their improved water vapour barrier performance [ 80 ].…”
Section: Factors Affecting Hydrophobicity Of Carrageenan Bionanocompo...mentioning
confidence: 99%
“… Water contact angle (WCA) values and the water vapour permeability (WVP) of sodium carboxymethylcellulose-carrageenan (CC) films alone and with self-assembled berberine-baicalin nanoparticles (CC/BB NPs) (taken from [ 80 ] with permission from the American Chemical Society). …”
Section: Figurementioning
confidence: 99%
“…[11][12][13][14][15] It is reported that berberine exhibits aggregation-induced emission characteristics, 16 and reactive oxygen species (ROS) are generated under white light irradiation, thus enhancing the antibacterial activity. [17][18][19] However, its low bioavailability and rapid metabolic elimination limit its application in anti-infective therapy. 20,21 One of the most effective approaches to improve its bioavailability is to prepare a berberine nanocomplex, which is also an efficient way to increase its bioactivity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Increased foodborne microbial illness has raised global concerns because it causes millions of deaths every year and continues to severely jeopardize public health worldwide. Consequently, this has motivated massive scientific research and investment in the design and development of novel and versatile antimicrobial materials to overcome microbial invasions and for preventing pathogenic infections. Controlling bacterial infections is critical not only for preventing global outbreaks but also for applications ranging from health care to improving daily life quality. , Over the past few years, there has been a significant increase in consumer interest in high-quality and safe food products. , Different strategies have been applied to develop new polymeric materials by incorporating antimicrobial agents to minimize the proliferation of microbes observed on various food packages. , Blending of polymers with conventional antibacterial agents has gained wide attention and has been applied to inhibit microbial growth in food products. , Data from previous studies clearly show that polymers can be functionalized with N-halamine precursors and related compounds, which could be a useful tool for the decontamination of food pathogens such as Listeria, yeasts, molds, and mesophiles found on solid surfaces. However, the leaching of conventional agents and the release of free chlorine from the materials pose a serious threat to human health and the environment. , Lately, photodynamic inactivation, a relatively novel technology, has emerged as a potential option for preventing microbial inhibition and preserving food quality and shelf-life . Nowadays, photoactive compounds have garnered considerable interest in the development of food packaging films because of their capability to produce oxidative biocide-reactive oxygen species (ROS) in many polymeric materials, durability for repeated uses, and lower-toxicity suitable for food contacts .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Lately, photodynamic inactivation, a relatively novel technology, has emerged as a potential option for preventing microbial inhibition and preserving food quality and shelf-life. 22 Nowadays, photoactive compounds have garnered considerable interest in the development of food packaging films because of their capability to produce oxidative biocide-reactive oxygen species (ROS) in many polymeric materials, durability for repeated uses, and lower-toxicity suitable for food contacts. 23 Under ultraviolet (UVA) exposure, photoactive nanoparticles have shown the ability to produce ROS such as singlet oxygen ( 1 O 2 ), hydroxyl radical ( • OH), and hydrogen peroxide (H 2 O 2 ).…”
Section: Introductionmentioning
confidence: 99%